2001
DOI: 10.2337/diacare.24.6.1023
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Plasma Glucose Concentrations on Microvascular Disease Between Pima Indian Youths and Adults

Abstract: OBJECTIVE—To examine whether the current adult guidelines for diagnosis of diabetes are applicable to youth (age <20 years). RESEARCH DESIGN AND METHODS—We analyzed fasting plasma glucose (FPG) and 2-h plasma glucose (PG) in two groups of Pima Indians, youths aged 5–19 years and adults aged 20–34 years, in relation to the incidence of microvascular disease when subjects were reexamined at ages 25–39 (youths) and 40–54 (adults). Microvascular disease was defined as retinopathy or a urine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…This recommendation included adult participants from the same study population we describe here, and we reported previously that HbA 1c and FPG measurements in adults were just as useful as 2hPG in predicting the risk of microvascular complications (16). Another study in this population found that a sharp rise in incidence of these complications occurred at the same level of glycemia in youth and adult cohorts; however, that study compared only FPG and 2hPG (17). …”
Section: Discussionmentioning
confidence: 90%
“…This recommendation included adult participants from the same study population we describe here, and we reported previously that HbA 1c and FPG measurements in adults were just as useful as 2hPG in predicting the risk of microvascular complications (16). Another study in this population found that a sharp rise in incidence of these complications occurred at the same level of glycemia in youth and adult cohorts; however, that study compared only FPG and 2hPG (17). …”
Section: Discussionmentioning
confidence: 90%
“…The participant was classified with type 2 diabetes if the fasting plasma glucose concentration was Ͼ7.0 mmol/l, the 2-h plasma glucose concentration was Ͼ11.1mmol/l, or there was an existing clinical diagnosis (as assessed by medical chart review). Standard anthropometric data were collected by trained observers with participants in lightweight clothing and no shoes as previously described in detail (10,12,16). No measures of puberty were available.…”
Section: Methodsmentioning
confidence: 99%
“…No measures of puberty were available. Metabolic variables were measured according to previously described methods (10,12,16). Statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective study of intensive insulin therapy in Japanese patients with type 2 diabetes mellitus showed significant reduction of progression of retinopathy, nephropathy, and neuropathy [62]. Several studies indicate that the risk of progression of microvascular disease is associated with both increased fasting and postprandial plasma glucose levels [63][64][65].…”
Section: Postprandial Hyperglycemia and Cardiovascular Diseasementioning
confidence: 98%